FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN CORPORATE GOVERNANCE DALAM LAPORAN TAHUNAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008-2011 - Rianto Jati Putranto; Surya Raharja (Diponegoro Journal of Accounting, 2013)
The research aims to analyze the effect of firm size, profitability, dispersion ownership, commisioners size, and audit quality on the disclosure of corporate governance which occurred by the Corporate Governance Disclosure Index, by a data set consisting of 16 bank company listed in Indonesia Stock Exchange .Population of this research is listed public company at Indonesia Stock Exchange with banking company as sample. The observation period made during the four years from 2008-2011. Sampling method uses purposive sampling method. Data analysis technique uses classic assumption test and hypothesis test uses multipleregression  analysisAgency theory is performed as a theory basic in research on corporate governance.The results of this research indicate that dispersion ownership and commisioners size positively affects the corporate governance disclosures. While the firm size, profitability, and audit quality are not significant affects the the corporate governance disclosures.